Attitudes and Perceptions of End-of-Life Dreams and Visions and Their Implication to the Bereaved Family Caregiver Experience. (July 2021) - Grant, Pei C.; Levy, Kathryn; Lattimer, Tahleen A.; Depner, Rachel M.; Kerr, Christopher W.
Background: While the majority of research assesses the impact of end-of-life dreams and visions (ELDVs) on patients, more recent research has begun to explore their impact on family caregivers (FCG). Objective: This study evaluates the relationship between general attitudes about dreams, perspectives of ELDV and their role the bereaved FCG experience. Design: Mixed-methods using a cross-sectional survey and five focus groups. Settings/Subjects: A total of 500 FCGs of patients who died under hospice care were recruited for the survey. Focus group members were self-selected through identified interest from the survey. Measurements: In addition to demographics and ELDV prevalence, general attitude toward dreams, ELDV perspectives, and impact on grief were assessed using ad hoc surveys. Results: Participants reporting ELDVs were significantly more validating of everyday dreams ( p < .001). Positive attitudes toward dreams strongly correlated with comfort from ELDVs for both patients and FCGs. Openness correlated positively with comfort from the ELDV for both the patient ( r = .149, p = .038) and FCG ( r = .217, p = 0.002) and negatively with fear/anxiety ( r = −.141, p = 0.050). Negative ELDV perceptions (ex. ELDVs were caused by medications) affected grief in areas such as accepting the loss ( r = −.235, p = .010) or maintaining connection ( r = −.255, p = .010) with the deceased. Focus group discussions were thematically analyzed resulting in 4 themes: ELDV narrative, Connection, Reflection, and Other Experiences . Conclusions: Positive general attitudes toward dreams and positive ELDV perceptions are correlated with better bereavement outcomes. Therefore, patient and family education on ELDVs that focuses on awareness and understanding of ELDVs may enhance clinical outcomes for both family and patients.